Pengaruh Persepsi Harga, Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Pada 212 Mart di Kota Langsa - Maulana Rahman; Syardiansah Syardiansah (Universitas Negeri Medan, 2021)
This study aims to determine the effect of price perceptions on purchasing decisions, to determine the effect of brand image on purchasing decisions, to determine the effect of product quality on purchasing decisions, and to determine the effect of perceived price, brand image and product quality simultaneously on purchasing decisions at Mart 212. in Langsa City. The population in this study are consumers who make purchases at 212 Mart in Langsa City. The exact population number is not known, so the sampling uses the unknown population formula. So that the number of samples in this study were 96 respondents. The results showed that price perception had no significant effect on purchasing decisions, brand image had a significant effect on purchasing decisions and product quality had a significant effect on purchasing decisions at 212 Mart in Langsa City. Simultaneously, price perception, brand image and product quality have a significant effect on purchasing decisions at 212 Mart in Langsa City. The coefficient of determination test results show that 71.6% of the variable price perception, brand image and product quality can explain the purchasing decision variables at 212 Mart in Langsa City.